The effect of restricted environments on selected postural, physiological and perceptual responses - Wolfe, Amy (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2008)
Manual lifting tasks are the predominant means of transporting materials in industry with many of these tasks being performed in confined spaces. Research has tended to focus on the biomechanical implications of working in small spaces with a decided lack of information about the physiological and perceptual responses in these environments. This holistic study therefore investigated the manner in which the human operator responded to conditions where the ceiling height was lowered and reach demands increased. Thirty-two young physically active male subjects (age: 21.55yr; stature: 1810mm) were recruited to complete a 2-way repeated measures experiment during which four lifting protocols where different combinations of ceiling height ('normal' or reduced to 1460mm in height) and reach demands (400mm or 800mm) were tested. A crude postural analysis was conducted while physiological responses were detailed and continuously monitored. Perceptual responses were also assessed. The tasks with a 'normal' ceiling height (mean compression forces: 2615N; mean shearing forces: 388N) and the greatest reach distance (mean compression forces: 3655N; mean shearing forces: 386N) placed individuals under the highest strain. Mean heart rate (HR) responses were significantly lower (p < 0.05) in the URN condition when compared to the RF condition. Furthermore, HR responses were statistically significantly affected by the height of the ceiling and the reach depth. Statistically significant differences (p< 0.05) in mean tidal volume (VT) occurred in the least (URN) and most (RF) restrictive conditions. Statistically significant differences (p < 0.05) in mean VE were evident between URN and URF, between URN and RF and between RN and RF. Ceiling height and reach demands had a statistically significant effect on all respiratory responses. There was a statistically significant difference in mean oxygen consumption (VO2) between the URN and all other conditions, and between the most restricted task (RF) and all other conditions. Both the effect of ceiling height and reach demands had a statistically statistically significant impact on VO2. Respiratory quotient (RQ) was significantly higher when loads were moved over 800mm compared to 400mm yet ceiling height did not have a statistically significant effect on RQ. Mean energy expenditure was significantly higher in the RF condition compared to the two least restrictive conditions (URN and RN). Statistically significant differences in EE were also evident between URN and RN, and between URN and URF. EE was significantly affected by reductions in ceiling height and increases in reach demands. Perceptually, the RF task (mean 'Central' RPE of 11) was perceived to place significantly greater cardiorespiratory demands on the operator compared to the URN (CRPE: 10) and RN (CRPE: 10) conditions. Statistically significant differences in perceived musculoskeletal strain only occurred between URN and RF. The effect of reach was perceived to have a statistically significant effect on both cardiovascular and musculoskeletal demands whereas ceiling height only had a statistically significant effect on musculoskeletal demands. The greatest discomfort was experienced in the lower back with the most intense discomfort occurring in the RN condition.
Keywords: Human engineering; Posture; Human mechanics; Work environment; Human beings -- Effect of environment on; Musculoskeletal system -- Wounds and injuries; Industrial safety; Work -- Physiological aspects; Stress (Physiology)